Youtubers As Micro-Celebrities And New Idols Among The IGeneration - Sugihartati, Rahma; Egalita, Nadia (Opción, 2019)
This article is the result of a qualitative study that examined the rise of You- Tubers as new idols among children as the iGeneration. Participants in this study were elementary school children aged between 9 years old and 12 years old who lived in urban areas. This study also suggested that leisure time or re- cess was used by children to access YouTube content – which often vary from short films, prank clips, online interviews with celebrities on their lifestyle, and other pop-culture related content. Both YouTubers are considered to be successful and influential as they have produced creative, entertaining, and hilarious content on the platform. Children are no longer idolizing the figures created by the popular culture industries like novels and film, but instead, they are starting to admire and recognize ordinary people who have created unique and interesting online content – or people who are social-media famous.